To translocate or not to translocate? Embedding population modelling in an inclusive structured decision-making process to overcome a conservation impasse - Parlato EH; Fischer JH; Steeves TE; Graydon K; Kennedy E; Makan T; Patterson E; Thurley T; Welch J; Parker KA (John Wiley and Sons Ltd on behalf of the Zoological Society of London, 2024)
The need for effective conservation strategies to combat the ongoing biodiversity crisis is well recognised. Conservation translocations are an important and frequently used form of conservation management for species recovery. Despite this, the uncertainty prevalent throughout the translocation cycle often makes it challenging to determine whether translocations should be included in the suite of actions to achieve desired conservation outcomes. Further, the fundamental question of whether translocations should occur is seldom assessed as a formal decision. We applied a formal decision analysis for the conservation management of a highly threatened bird (karure | kakaruia | Chatham Island black robin | Petroica traversi) to evaluate whether translocation and/or other actions should be implemented for species recovery. The species' precarious status (<330 adults), combined with uncertainty about translocation outcomes, meant that for years, decision-makers were reluctant to act given the potentially severe consequences of translocation failure. We used structured decision-making in conjunction with population modelling to estimate the consequences of translocations and other actions across a range of objectives identified by Moriori and Ngāti Mutunga o Wharekauri (Indigenous Peoples of Rēkohu | Wharekauri | the Chatham Islands), the local community and government agencies. Structured decision-making facilitated an inclusive approach that ensured all participants were actively engaged in the decision-making process including the identification of the best management alternative while balancing multiple objectives. This process overcame the long-standing conservation impasse, resulting in rapid implementation of actions, including translocation, that would have otherwise been difficult to achieve. The preferred alternative across objectives involved multiple translocations, illustrating the vital role translocations have in the desired future management for the species. The methods used in our study can be readily applied in other species recovery programmes to help decision-makers navigate the complexities and uncertainties inherent in conservation decisions.
Keywords: Decision analysis; population model; expert elicitation; reinforcement; threatened species; management; translocations; Petroica traversi